Critical appraisal of the learning curve of minimally invasive hepatectomy: experience with the first 200 cases of a Southeast Asian early adopter. Issue 6 (20th January 2020) - Goh, Brian K. P.; Prieto, Mikel; Syn, Nicholas; Koh, Ye‐Xin; Lim, Kai‐Inn
Abstract: Background: A recent study analysing the experience of fellowship‐trained early adopting surgeons during stage 3 of the IDEAL paradigm demonstrated that the learning curve (LC) of minimally invasive hepatectomy (MIH) can be shortened compared to the long steep LC of pioneering surgeons. In this study, we aimed to critically appraise the contemporary learning experience with MIH of a 'self‐taught' early adopter during stage 3 of the IDEAL paradigm. Methods: A review of the first 200 patients who underwent MIH over an 88‐month period since 2011 by a single surgeon who had no prior training in MIH was conducted. The cohort was divided into four groups of 50 patients. Risk‐adjusted cumulative sum analysis of the LC was performed. Results: Two hundred patients underwent MIH and there were 13 (6.5%) open conversions. There were 55 (27.5%) major resections and 94 (47.0%) were graded as high/expert difficulty according to the Iwate criteria. Fifty‐one (25.5%) patients had cirrhosis and 98 (49%) had previous abdominal surgery including 28 (14%) with previous liver resections. There were five (2.5%) major (Grade 3b–5) morbidities, zero 30‐day mortality and one (0.5%) 90‐day mortality. Comparison across the four groups demonstrated a significant trend towards increased adoption of total MIH, increased multifocal tumours, increased performance of major hepatectomies and decreased blood loss. Risk‐adjusted cumulative sum analysis demonstrated that the LC in terms of blood loss, blood transfusion rate, open conversion rate, operation time and post‐operative length of stay to be 65 cases. The LC for MIH of Iwate low/intermediate difficulty and of Iwate high/expert difficulty were 35 and 30 cases, respectively. Conclusion: MIH of all difficulty levels is feasible and can be safely adopted today even by surgeons with no prior formal training. The LC of the 'self‐taught' early adopter is about 65 cases. Abstract : Minimally invasive hepatectomy of all difficulty levels is feasible and can be safely adopted today even by surgeons with no prior formal training. The learning curve of the 'self‐taught' early adopter is about 65 cases.